2019
DOI: 10.1016/j.celrep.2019.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick Type C Disease Reveals a Link between Lysosomal Cholesterol and PtdIns(4,5)P2 That Regulates Neuronal Excitability

Abstract: SUMMARY There is increasing evidence that the lysosome is involved in the pathogenesis of a variety of neurodegenerative disorders. Thus, mechanisms that link lysosome dysfunction to the disruption of neuronal homeostasis offer opportunities to understand the molecular underpinnings of neurodegeneration and potentially identify specific therapeutic targets. Here, using a monogenic neurodegenerative disorder, NPC1 disease, we demonstrate that reduced cholesterol efflux from lysosomes aberrantly modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 63 publications
1
52
0
Order By: Relevance
“…Using mice bearing a mutation in the NPC1 gene that is similar to a common one in NPC patients, we demonstrated that NPC1 defects have a profound impact on synapses. Very recently, a link between lysosomal cholesterol and neuronal firing patterns has been revealed in neurons upon NPC1 pharmacological inhibition or genetic mutation [42]. NPC1 mediates the cholesterol redistribution and CYP46A1 and AMPA receptor dynamism necessary for LTP, which drives the postsynaptic plasticity required for learning and memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using mice bearing a mutation in the NPC1 gene that is similar to a common one in NPC patients, we demonstrated that NPC1 defects have a profound impact on synapses. Very recently, a link between lysosomal cholesterol and neuronal firing patterns has been revealed in neurons upon NPC1 pharmacological inhibition or genetic mutation [42]. NPC1 mediates the cholesterol redistribution and CYP46A1 and AMPA receptor dynamism necessary for LTP, which drives the postsynaptic plasticity required for learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Independently of a deficiency in extracellular factors, our results highlight the intrinsic failure of a synaptic cholesterol-dependent mechanism impairing LTP in NPC1 mutant mice. Very recently, a link between lysosomal cholesterol and neuronal firing patterns has been revealed in neurons upon NPC1 pharmacological inhibition or genetic mutation [42]. Alterations in lysosomal cholesterol egress transcriptionally upregulate the ABCA1 transporter, leading to reduced levels of phosphoinositides at the plasma membrane, which in turn decrease a voltage-gated potassium channel and enhance excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Another target for which ligands have not yet been validated is the KCNQ2/3 channel (also named M channel or Kv7.2/7.3 channel). It has been shown in NPC1 disease that reduced cholesterol efflux from lyso somes aberrantly modifies neuronal firing patterns 324 . This disruption of lysosomal cholesterol efflux with decreases in PtdIns(4,5)P2dependent KCNQ2/3 chan nel activity may lead to the aberrant neuronal activity.…”
Section: Emerging Potential Lysosomal Therapeutic Targetsmentioning
confidence: 99%
“…Dysfunction in the activity of KCNQ2/3 or altered levels of PtdIns(4,5)P2, due notably to genetic mutations, might also be involved in other neuropathies (for example, some forms of epilepsy, HD, PD, AD, ALS and Friedrich ataxia). Although further experiments are needed to validate the link discovered between hyperexcitability and cell death in NPC1 disease and other neurodegenerative diseases, small molecules such as retigabine, an anti convulsant drug that keeps KCNQ2/3 channels open, might rep resent important therapeutic tools 324,325 . Other channel opener ligands of KCNQ2/Q3 include ICA069673 and its derivatives.…”
Section: Emerging Potential Lysosomal Therapeutic Targetsmentioning
confidence: 99%
“…Subsequently, the activity of interneurons is likely to be increased, resulting in an elevated GABAergic synaptic transmission to the postsynaptic Purkinje cells, and consequently not able to be further elevated by NMDA. In addition, a dysfunction of KCNQ1/2 leading to hyperexcitability of NPC1-deficient neurons might contribute to this effect [20].…”
Section: Discussionmentioning
confidence: 99%